Enhanced solubilization and biochemical methane potential of waste activated sludge by combined free nitrous acid and potassium ferrate pretreatment. (February 2020) - Wang, Jinsong; Zhang, Zhaoji; Ye, Xin; Pan, Xiaofang; Lv, Nan; Fang, Hongda; Chen, Shaohua
Graphical abstract: Highlights: FNA + PF pretreatment increased TSS removal of WAS than either FNA or PF pretreatment. FNA + PF pretreated WAS showed extremely high BMP during subsequent anaerobic digestion. FNA + PF pretreatment promoted the enrichment of Methanolinea, Mesotoga, and Methanobacterium . FNA + PF pretreatment stimulated flexible pathways of methanogenesis during anaerobic digestion. Abstract: The increasing production of waste activated sludge (WAS) from wastewater treatment plants presents an inherent environmental burden. In this study, Free nitrous acid combined with potassium ferrate (FNA + PF) pretreatment was used to enhance solubilization and biochemical methane potential of WAS. Results indicated that the maximum removal rates of total suspended solid by PF, FNA, and PF + FNA pretreatment were 21.84%, 38.09%, and 56.17%, respectively. The biochemical methane potential of WAS without pretreatment reached 61.22 L CH4 /kg VSS added while this value increased to 147.07 L CH4 /kg VSS added after FNA + PF pretreatment (0.06 g/g TSS NaNO2 and 0.25 g/g TSS K2 FeO4 ). Shotgun metagenomic analysis revealed that FNA + PF pretreatment could increase the diversity and stability of microbial communities by shifting methanogenic pathways from strictly acetoclastic to acetoclastic/hydrogenotrophic, thereby enhancing methane production. This study suggested that FNA + PF pretreatment is a promising technology to reduce WAS and enhance methane production by pretreated WAS during anaerobic digestion.